Development of the RF power distribution system for the ILC prototype cryomodule - Joshi Prakash; Kako Eiji; Matsumoto Toshihiro; Michizono Shinichiro; Omet Mathieu; Yamamoto Yasuchika (EPJ Web of Conferences)
The sub-local power distribution system (sub-LPDS) for the International Linear Collider (ILC) is being redesigned to satisfy the requirements. Its main features are a design with sub-LPDS within the cryomodule (CM) length, a low center of gravity, and a reduced number of waveguide components. Further, we considered to update the ILC power distribution system based on the ILC prototype design. The ILC prototype CM bunker wall’s thickness will likely be limited, so a sub-LPDS with low field-emission was also designed. The sub-LPDS is planned to be mounted onto the CMs before tunnel installation at the ILC. Therefore, a prototype sub-LPDS support system was designed. A test assembly was conducted to better understand the installation process and space requirements. Furthermore, a concept of a sub-LPDS without a circulator was introduced. This concept was evaluated by analytical calculations, simulations, and low-power tests.